INTEGRASI FAKTOR KLINIS, FISIOLOGIS, PSIKOLOGIS, INTERVENSI TERHADAP OUTCOME CABG ON-PUMP: SCOPING REVIEW - Wan Nishfa Dewi; Maizirwan Maizirwan; Raja Asmalinda (Jurnal Keperawatan Abdurrab, 2026)
This study aims to comprehensively integrate the clinical, physiological, psychological, and intervention factors that affect patient outcomes after coronary artery bypass grafting (CABG) surgery using on-pump techniques, as well as to identify research gaps in the scientific literature. This study uses a scope review design with a systematic approach using the Scopus Preview, Web of Science (WoS) database, which focuses on leading journal articles (Q1–Q4). The selection process followed the PRISMA guidelines, resulting in 20 studies that met the inclusion criteria. The data is extracted from the form of the graph and analyzed thematically. The results showed that clinical factors such as age, sex, and comorbidities were the dominant determinants of outcomes, followed by physiological factors associated with hemodynamic changes and inflammatory responses induced by cardiopulmonary bypass. Psychological factors such as anxiety, depression, and quality of life also play a role in the recovery process, although there is still a limited amount of research. Interventions found included Enhanced Recovery After Surgery (ERAS), cardiac rehabilitation, prehabilitation, and pharmacological and psychological interventions with varying degrees of effectiveness. The conclusion of this study shows that patient outcomes after CABG with on-pump techniques are influenced by multidimensional interactions, but the existing literature is still fragmented and has not been comprehensively integrated